Application of the Home Room Technique in Improving Learning Discipline of PGRI Banyuwangi Middle School Students: Penerapan Teknik Home Room Dalam Meningkatkan Kedisplinan Belajar Siswa SMP PGRI Banyuwangi - wulandari, putri; Napisah, Siti; Wahyu Prasetyo, Fajar (BIMBINGAN DAN KONSELING BANYUWANGI, 2024)
This research was conducted to determine the application of the home room technique in improving the learning discipline of PGRI Banyuwangi Middle School students. This research uses a quantitative method, equivalent control group design. This research sample used purposive sampling. The sample selection obtained was 12 students from a total of 40 students who were included in the low learning discipline category. Research results (Hernia, 2023) if tcount > t table, then Ho is rejected and Ha is accepted. This means that the significance obtained is smaller than 0.05, because of the sig testing method. (2-tailed) < 0.05 then Ho is rejected and Ha is accepted. Which means 0.000 < 0.05, thus Ho is rejected and Ha is accepted, where Ha reads "Home Room Engineering group guidance is effective in improving learning discipline at PGRI Banyuwangi Middle School." accepted.